The Use of Carbon Dioxide Released from Coconut Shell Combustion to Produce Na2CO3 - Simanjuntak, Wasinton; Sembiring, Simon; Zakaria, Wan Abbas; Pandiangan, Kamisah D (Makara Journal of Science, 2014)
In this investigation, sodium carbonate (Na2CO3) was produced by reacting the CO2 released from coconut shell combustion with NaOH solution with molar concentrations of 6.5, 7.0, 7.5, and 8.0 M. The main purpose of the study was to assess the potential of the proposed method for mitigation of the CO2 gas released into the atmosphere by the coconut shell industry. The Na2CO3 powder produced was oven-dried at 110 oC and subsequently characterized using FTIR, XRD, and SEM/EDS techniques. Thermal analysis was also carried out using DTA/TGA to investigate the thermal mechanisms of sodium carbonate formation. The experimental results show that the concentration of NaOH influences the mass of sodium carbonate produced, with the highest mass of 190.6 g obtained using 7.0 M NaOH solution. The FTIR analyses show the existence of O-H, C-O, C=O, and CO3 -2, confirming the formation of Na2CO3. The C-S functional group was also detected most likely due to the presence of the sulfur that naturally exists in the coconut shell. The formation of Na2CO3 is also supported by the presence of C, Na, and O on the EDS results and the presence of the thermonatrite (Na2CO3.H2O) phase, as seen by the XRD. The XRD analysis of the sintered sample at 450 oC indicates the transformation of thermonatrite into sodium carbonate and sodium oxide, which is in accordance with the results of DTA/TGA analysis. Based on the results obtained, it is concluded that the proposed method can be applied to mitigation of CO2 gas released by the coconut shell industry.